Barriers and facilitators to provide multidisciplinary care for breast cancer patients in five Latin American countries: A descriptive-interpretative qualitative study - Carlos Barrios; Guillermo Sánchez-Vanegas; Cynthia Villarreal-Garza; Andrés Ossa; Milton A. Lombana; Angélica Monterrosa-Blanco; Ana S. Ferrigno; Carlos Alberto Castro (Elsevier, 2022)
Summary: Background: Multidisciplinary care (MDC) remains a cornerstone for breast cancer management as it is associated with improved quality of care and patient outcomes. However, the adoption of MDC practice is heterogeneous and has been poorly explored in Latin America. The objective was to describe barriers and possible facilitators for providing MDC to breast cancer patients in five Latin American countries. Methods: A panel of experts with an active clinical practice in Bolivia, Colombia, Ecuador, Mexico, and Uruguay was convened to identify barriers and facilitators to MDC. This study is a qualitative synthesis of a structured discussion regarding the state of MDC in the setting of breast cancer. Findings: Experts recognized that most oncology practices in Latin America do not apply a multidisciplinary approach for breast cancer patients. Predominant barriers for MDC are fragmentation of health services, being understaffed, inadequate infrastructure, and geographic disparities. Access to MDC varies widely in the region, with significant heterogeneity documented within countries. MDC practice was described as being more common in the private sector in Ecuador and Uruguay, while it is more widely implemented in public institutions of Colombia and Bolivia. Interpretation: Establishing quality MDC remains a challenge for oncology practices in Latin America. Addressing regional issues and identifying specific local needs is warranted to encourage the adoption of an effective multidisciplinary approach and, consequently, improve clinical outcomes. Active involvement of all stakeholders is required to build locally solutions and should involve institutions, health professionals, and patients. Funding: Research was funded by Productos Roche S.A.